METODE DAKWAH ABANGAN DAN PUTIHAN WALISONGO DI JAWA: ANTARA SUNAN KALIJAGA DAN SUNAN GIRI - Al Faruq, Muhammad Saifudin; Rohman, Fathur (IIQ An Nur Yogyakarta, 2025)
AbstractThe beginning of the spread of Islam in the archipelago began in the 11th century in the Malacca Peninsula, spread by merchants from the Middle East. Meanwhile, Islam began to establish itself in Java in the 14th century along with the collapse of the Majapahit kingdom. The method used in this research is a qualitative method, using a descriptive approach. The data collection methods used by researchers are interview methods and library research. The specifics of this research are the dualism of the Walisongo preaching school, especially the abangan method used by Sunan Kalijaga and the Putihan method used by Sunan Giri. As a result of this dualism, there was a division of Muslims in Java, so that it became known as Abangan Islam and Putihan Islam. Abangan Muslims tend to worship using art, for example using Javanese musical compositions or songs, while White Muslims worship based on the Koran and hadith in a Kaffah (perfect) manner, they consider worshiping using art to be shirk. Keywords : Walisongo Da'wah, Putihan School, Abangan School, Sunan Kalijaga, Sunan Giri